2020
DOI: 10.3390/nu12092658
|View full text |Cite
|
Sign up to set email alerts
|

Dissatisfaction with Body Weight among Polish Adolescents Is Related to Unhealthy Dietary Behaviors

Abstract: The aims of the study were to determine the socio-demographic factors that may affect body weight dissatisfaction and to analyze the relationship between eating habits and dissatisfaction with body weight among a national random sample of Polish adolescents aged 13–19 years. Data on gender, age, level of education, body weight status, screen time, body weight satisfaction and selected nutritional behaviors were collected using a questionnaire. Body mass status was assessed based on weight and height measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Other lifestyle behaviors in the present study did not significantly associate with BD. However, a study conducted among Polish adolescents aged 13–19 years demonstrated that being girls, older participants (17–19 years old), overweight or obese adolescents and having higher screen time (over 4 h) were more likely to be dissatisfied with their body weight ( Wawrzyniak et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other lifestyle behaviors in the present study did not significantly associate with BD. However, a study conducted among Polish adolescents aged 13–19 years demonstrated that being girls, older participants (17–19 years old), overweight or obese adolescents and having higher screen time (over 4 h) were more likely to be dissatisfied with their body weight ( Wawrzyniak et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Children were asked to fill in a short questionnaire assessing their demographics characteristics (age, gender, school) as well as opinions and practices with regard to their body weight: Perceived weight—children were asked how they considered their weight, the possible answers being normal, too low, too big. A similar approach was used by other studies, too [ 10 , 11 , 12 , 13 , 15 , 18 , 19 ]. Weight management practices in the last year (attempts to lose weight, nothing or attempts to gain weight in the last year); Types of methods used in the last year for losing weight if they had tried to do this (children could choose from sport, dieting, consumption of special tea, use of medicine, vomiting, and massage); If they discussed about their weight with their parents in the last year (yes/no) If they discussed issues focused on their weight with health professionals in the last year (yes/no) …”
Section: Methodsmentioning
confidence: 99%
“…Perceived weight—children were asked how they considered their weight, the possible answers being normal, too low, too big. A similar approach was used by other studies, too [ 10 , 11 , 12 , 13 , 15 , 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, male adolescents are more likely to engage in physical activities than female adolescents [ 8 , 9 ]. Female adolescents may be more concerned with their dietary behaviors, because they pay more attention to their body image or body shape [ 10 , 11 , 12 ]. Female adolescents are known to drink less alcohol than male adolescents [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%